The Social Status Of Judo Athletes - Popovic, Dragan; Boli, Evagelia; Popovic, Milos; Savic, Vladimir; Popovic, Jasna (European Scientific Journal, ESJ, 2016)
The research aimed to determine the social status structure of male and female judo athletes. In order to determine the social status structure a total of 200 athletes (100 males and 100 females) were examined. To assess the social status, a model designed by Saksida and Petrovic as well as Appendix INST2 and questionnaire SSMIN (Boli, Popovic, Karanov & all 2015) were applied. All the data in this study were processed at the Multidisciplinary Research Center of the Faculty of Sport and Physical Education, University of Pristina, through the system of data processing software programs DRSAOFT developed by Popovic, D. (1980,1993) and Momirovic, K. & Popovic , D. (2003). The algorithm and program applied in this study are fully presented and the results of this program are analyzed. In order to determine the latent structure of social status of judo athletes, a method of component factor analysis was used. Using component analysis of variables for assessing the social status of judo athletes and applying Momirovic`s B6 criterion, three characteristic roots which can be considered statistically significant were obtained. The total percentage of the explained variability of the applied system of variables is 37.45%. By examining Table 1, it can be seen that the first characteristic root extracts 18.75% of the explained variance, the second - 10.21%, and the third only 8.45%.